Falls in Patients of Medical Institutions in South Korea: A Literature Review - Jongwon Choi; Woochol Joseph Choi (Korean Research Society of Physical Therapy, 2023)
Background: Like many other countries, falls and related injuries in older adults are great concerns in South Korea. In particular, falls are common in medical institutions, often causing the increase of the length of hospitalization. Objects: The purpose of this review was to help understand and address falls in hospitalized individuals in South Korea. Methods: The review was conducted on literature published in Korean from 2010 to 2022, searched in the Korea Citation Index and PubMed. Keywords used for the search were as follows: falls, fall risk, fall risk assessment, hospital, inpatient, intervention, Korea, and prevention. Results: A total of 54 articles were found and reviewed. The most common place of fall accidents was the inpatient room, where there were many cases of falls while walking. Loss of balance was the most common cause of falls, and many falls occurred in patients admitted to the internal medicine. Furthermore, a risk of falling increased with the type of medications taken. In terms of tools to assess patients' fall risk, the Morse Fall Scale (MFS) was commonly used. Patient-specific fall prevention activities were common to address falls, and they decreased the frequency of falls and the fear of falling. Factors influencing the effectiveness of the fall prevention activities included attitudes toward falls, education, environmental factors, patient safety culture, and self-efficacy in preventing falls. Conclusion: Our results should help understand and address falls and injuries in medical institutions.